SYNTHESIS AND PROPERTIES THE SYSTEM OF YxYBa2–xCu4O8±Δ, (0.05£х£0.2): UDC 546. 65' 56' 431 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
YBa2Cu4O8±d and YxYBa2–xCu4O8±d (0.05£х£0.2) systems were synthesized using co-precipitation and ceramic methods. Dependence of parameters and kinds of lattice symmetry of YxYBa2–xCu4O8±d from the displacement degree x was studied. At research of electric conductivity of samples YxYBa2–xCu4O8±d (0.05£х£0.2) it is positioned, that all samples pass in a superconducting condition at temperatures above 77 K.
Keywords: -